Beta-Alanine Supplementation Improved 10-km Running Time Trial in Physically Active Adults - Santana, Jeferson O.; de Freitas, Marcelo C.; dos Santos, Diana M.; Rossi, Fabrício E.; Lira, Fabio S.; Rosa-Neto, José C.; Caperuto, Erico C. (Frontiers in Physiology, 2018)
The purpose of this study was to investigate the effects of β-alanine supplementation on a 10 km running time trial and lactate concentration in physically active adults. Sixteen healthy subjects were divided randomly into two groups: β-alanine (n = 8) and placebo group (n = 8). The experimental group ingested 5 g/day of β-alanine plus 1 g of resistant starch, and control group ingested 6 g of resistant starch, both for 23 days. Time to complete a 10-km running time trial and lactate concentration following the test were assessed at baseline and post 23 days. The running training program was performed three times per week on non-consecutive days (day 1: running 7 km; day 2: six sprints of 500 m at maximum speed with 2 min of recovery; day 3: running 12 km). The time to complete a 10-km running time trial decreased significantly only for the β-alanine group (Pre = 3441 ± 326.7, Post = 3209 ± 270.5 s, p < 0.05). When analyzing the delta (Time post minus Time at baseline value) there was a statistically significant difference between the β-alanine vs placebo group (-168.8 ± 156.6 vs. -53.60 ± 78.81 s, p = 0.007), respectively. In addition, the β-alanine group presented lower blood lactate concentration after the 10-km test (β-alanine: Pre = 8.45 ± 1.94 vs. Post = 6.95 ± 2.44 mmol/L; Placebo: Pre = 8.7 ± 3.0 vs. Post = 10.8 ± 2.5 mmol/L, p = 0.03). In conclusion, β-alanine supplementation improved the 10-km running time trial and reduced lactate concentration in physically active adults.